Methodology for determining the mean and extreme sea level regimes (astronomical and meteorological tides) considering scarce records in microtidal zones: colombian Caribbean case (2018)
Synthetic sea level (SL) records of the Cartagena Bay and the Urabá Gulf, from 1991 to 2010, were obtained through this methodology. Simulated series were adjusted against different probability functions (e.g. Log-Normal, Normal, Weibull, Gumbel). Normal and Gumbel distributions provided the best fit for mean and extreme regimes, respectively. Within the Cartagena Bay, there were no significant differences in the mean regime; whereas for the Urabá Gulf its magnitude increased as much as twice southward. Moreover, the extreme regime exhibited the largest values in the southern sector of the Urabá Gulf. This methodology might be implemented in areas where sea level records are scarce or poorly reliable. Thus, it may valuable for planning and building port and coastal infrastructure, as well as for implementing risk reduction measures.